Differentiation and species status of the Neotropical yellow-eared bats Vampyressa pusilla and V. thyone (Phyllostomidae) with a molecular phylogeny and review of the genus - Lim, Burton K.; Pedro, Wagner André [UNESP]; Passos, Fernando C. (Museum & Inst Zoology Pas-polish Acad Sciences, 2003)
A systematic re-evaluation of Vampyressa pusilla warrants the elevation of V. p. thyone from subspecies to species rank based on its distinction from the allopatric V. p. pusilla. Morphological, mensural, chromosomal, and mitochondrial differences define each of these two taxa as divergent lineages. Vampyressa pusilla is endemic to the Atlantic Forest of southeastern South America and V. thyone is found allopatrically in northwestern South America, Central America, and southern Mexico. A molecular phylogenetic analysis of the mtDNA ND3-4 gene region using restriction endonuclease cut sites resulted in a monophyletic, although weakly supported Vampyressa ingroup with Chiroderma, and a clade of Mesophylla and Ectophylla as successive basal outgroup lineages. The phylogeny within Vampyressa, with the exception of V. melissa which is most similar to V. thyone based on karyotypes and morphology, had a topology of ((pusilla + thyone) + ((brocki + nymphaea) + bidens))).
Keywords: Chiroderma; Ectophylla; Mesophylla; Morphology; Phyllostomidae; Restriction site mapping; Vampyressa; Vampyressa pusilla; Vampyressa thyone; Bat; Phylogeny; Taxonomy; Bidens; Melissa; Nymphaea; Thyone; Vampyressa melissa